Arte e tabù: il disgusto e i limiti della rappresentazione (Materiali di Estetica. Terza serie, 2022)
Referring to the notion of representation, I will argue the idea that disgust continues to constitute a limitation for art and that the presence of the disgusting can be read through the Freudian notion of taboo. The indulgence of artistic creation in disgust, in fact, would confirm the fact that only what is domesticated, thus what does not arouse authentic disgust, can be assimilated by art. On the contrary, authentic disgust remains taboo insofar as it indicates the absolutely other, the unassimilable, a non-domesticated animality extraneous to the process of civilization. It is, after all, what classical aesthetics had already shown and that today can be reread in Freudian terms.
Keywords: Disgust; Taboo; Art; Representation; Limits